Analisis Frasa Verba dan Frasa Nomina dalam Teks Argumentasi pada Buku Ajar Kelas XI SMA Kurikulum Merdeka - Itsnaini Nur Khasanah; Dea Sheva Dwi Anggraeni; Kholifatun Nisya; Rossa Farhana Ridho Susanti; Asep Purwo Yudi Utomo; Uki Hares Yulianti (Student Scientific Creativity Journal, 2023)
This research analyzed one of the syntactic fields of study, namely phrases in argumentation texts in class XI textbooks of the Kurikulum Merdeka. Two data will be studied in argumentation texts entitled "Ketahanan Pangan Lokal” and “Ketahanan Pangan pada Masa Pandemi Covid-19". In this study, the researchers limit the analysis of phrase type studies, namely based on word categories in the form of verb and noun phrases. The purpose of this research is to know in depth the research data along with an explanation of the types of phrases based on word categories, namely verb phrases and noun phrases found. In addition, this research is also expected to be valuable as a learning medium, especially in one of the fields of syntactic units, namely about phrases. The research method used a qualitative descriptive methodological approach and theoretical syntax with reading, listening, and recording techniques. In the analysis, it was found that verb phrases based on their position and location were divided into two, namely Coordinative Verb Phrases (FVK) and Subordinative Verb Phrases (FVS). Meanwhile, noun phrases based on their position and location are also divided into two, namely Coordinative Noun Phrases (FNK) and Subordinative Noun Phrases (FNS). To facilitate the analysis and understanding of the reader, the phrase data is presented in the form of a table accompanied by an explanation. This research is important to analyze the phrases in the argumentation text contained in the independent curriculum textbook, this is because the independent curriculum is the latest educational learning system in Indonesia.